Non-isolated multiple input multilevel output DC-DC converter for hybrid power system - Ameen M. Al-Modaffer; Amer A. Chlaihawi; Husam A. Wahhab (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The utilization of multisources of energy in a compact and an effective power system gains an essential role in power electronic industry. As such, the design and simulation of a new non-isolated multiple input multilevel output (MIMLO) DC-DC converter for hybrid power system is presented. The MIMLO DC-DC converter can be integrated in renewable energy, such as fuel cells, wind turbines and photovoltaic arrays etc, to get the best output voltages. The MIMLO DC-DC converter powers the load from renewable energy sources through the independence of the availability of other sources. The proposed topology has been simulated by using MATLAB/Simulink software to testify the performance control operation of the multiple input multilevel output DC-DC converter. The results of the carried-out simulation favor the usage of multi-input voltage, rather than a single input voltage. The MIMLO design has the advantages of a simple configuration, reduced number of switches, fewer components, high efficiency, and high conversion ratio. The multilevel output DC-DC converter provides high voltage transfer with low size inductors, reduction of losses, low stress voltage on switches and diodes.